Analisis Kinerja Perusahaan Dengan Metode Balanced Scorecard Periode 2013-2014 (Studi Kasus Pada Hotel Sahid Bandar Lampung). - Tia Rizna Pratiwi; Herry Goenawan Soedarsa; Made Diah Ratna (Jurnal Akuntansi dan Keuangan, 2018)
This research aims to meansure the performance of Sahid Hotel using the balanced scorecard method with four perspectives in balanced scorecard measurement. The four perspectives of balanced scorecard are financial perspective, customer perspective, internal business perspective, and learning and growth perspective. This research using data during two periods 2013-2014. The result of this research using balanced scorecard such as financial perspective, customer perspective, and learning and growth perspective show quite less, but to internal business show quite good. From four perspective of balanced scorecard method, over all performance of Sahid Hotel is less.